Legal Protection for Airline Passengers Experiencing Loss of Cabin Baggage During Flights - Situmorang, Josua Pebruanto Mangihut; Purba, Hasim; Sunarmi, Sunarmi; Harianto, Dedi (LOCUS MEDIA PUBLISHING, 2024)
Airplanes frequently transport passenger baggage, which may be susceptible to loss or damage. The case of Leo, who lost valuable items during a flight from Geneva to Jakarta with Qatar Airways, highlights this issue. The thesis entitled “Analysis of Legal Protection for Airline Passengers Experiencing Loss of Cabin Baggage during Flights (A Study of Supreme Court Decision No. 117PK/Pdt.Sus-BPSK/2017)” examines: 1) regulations regarding legal protection for passengers; 2) the liability of airlines; and 3) an analysis of the Supreme Court ruling concerning legal protection for passengers. The research method employed is normative juridical with a legislative approach and case studies. The data analyzed is secondary, with conclusions drawn deductively. The findings indicate that legal protection and compensation for passengers are governed by Law No. 1 of 2009 and the Minister of Transportation Regulation No. 77 of 2011. The liability of airlines includes the obligation to pay compensation if the passenger can demonstrate the fault of the airline staff. It is recommended that the government formulate regulations related to the proof of damage or loss of baggage.